Method of test pool synthesis for an intelligent high-density IoT edge-layer gateway - Panchenko, Volodymyr; Kuchuk, Heorhii; Noskov, Valentin Ivanovich; Leonov, Sergey; Lipchanska, Oksana (Національний технічний університет "Харківський політехнічний інститут", 2026)
Relevance. High-density IoT environments are characterized by a large concentration of sensors and devices that exchange data intensively within a limited space. Under such conditions, edge-layer intelligent gateways become particularly important. These gateways can locally process information, optimize traffic, and ensure consistent interaction among heterogeneous devices. The development of a test pool for an edge-layer intelligent gateway in high-density IoT is relevant due to the rapid growth in the number of connected devices and the increase in their spatial density. In such conditions, the gateway must maintain stable operation despite high levels of radio interference and competition for network resources. An additional challenge is the heterogeneity of the IoT environment, as devices use different protocols, have different data formats, and exhibit diverse load profiles. Without a specially constructed test pool, it is impossible to reliably evaluate the behavior of the gateway under a realistic mix of technologies and topologies. However, due to substantial heterogeneity, the space of possible test-pool configurations has very high dimensionality. Moreover, there are significant time and resource constraints associated with operating the test pool. The subject of this study is the methods for constructing test pools. The purpose of the article is to develop a method for synthesizing a test pool for an edge-layer intelligent gateway in high-density IoT. The following results were obtained. A fivelayer architecture of an edge-layer intelligent gateway for high-density IoT is proposed. The operational specifics of the gateway and the particular aspects of its testing are identified. The task of synthesizing the test pool is reduced to a combinatorial problem of selecting an optimal configuration within an extremely large state space. To solve it, the use of a classical genetic algorithm is proposed. The proposed algorithm made it possible, within an acceptable time, to obtain a test pool with nearly minimal execution time, a minimal number of tests, and maximal coverage of the gateway components. Conclusion. The proposed method enables the construction of a test pool for an intelligent gateway within a high-dimensional state space while meeting the specified requirements. Future research concerns the development of a method for reducing the dimensionality of the state space of individual tests for gateway components.

Актуальність. Високощільні ІоТ-середовища характеризуються великим скупченням сенсорів і пристроїв, які інтенсивно обмінюються даними в обмеженому просторі. За таких умов особливої ваги набувають інтелектуальні шлюзи граничного шару. Такі шлюзи здатні локально обробляти інформацію, оптимізувати трафік і забезпечувати узгоджену взаємодію різнорідних пристроїв. Розробка тестового пулу для інтелектуального шлюзу граничного шару високощільного IoT є актуальною через швидке зростання кількості підключених пристроїв та збільшення їх просторової щільності. У таких умовах шлюз має забезпечувати стабільну роботу попри високий рівень радіоперешкод і конкуренцію за мережеві ресурси. Додатковою проблемою є гетерогенність IoT-середовища, тому що пристрої використовують різні протоколи, мають різні формати даних і різні профілі навантаження. Без спеціально сформованого тестового пулу неможливо надійно оцінити поведінку шлюзу за умов реалістичного міксу технологій та топологій. Але внаслідок суттєвої гетерогенності простір можливих варіантів формування пулу має велику розмірність. Крім того, існують суттєві часові та ресурсні обмеження при експлуатації тестового пулу. Предметом вивчення в статті є методи формування тестових пулів. Метою статті є розробка методу синтезу тестового пулу для інтелектуального шлюзу граничного шару високощільного ІoТ. Отримано такі результати. Запропонована п’ятирівнева архітектура інтелектуального шлюзу граничного шару високощільного ІoТ. Визначені особливості функціонування шлюзу та специфічні особливості при проведенні його тестування. Задача синтезу тестового пулу зведена до комбінаторної задачі вибору оптимальної конфігурації у дуже великому просторі станів. Для її розв’язання запропоновано використовувати класичний генетичний алгоритм. Запропонований алгоритм дозволив за прийнятний час отримати тестовий пул з практично мінімальним часом виконання, мінімальною кількістю тестів та максимальним покриттям компонент шлюзу. Висновок. Запропонований метод дозволяє у просторі станів великої розмірності сформувати тестовий пул для інтелектуального шлюзу, який відповідає заданим вимогам. Напрям подальших досліджень стосується розробки методу зменшення розмірності простору станів окремих тестів компонент шлюзу.
Метод синтезу тестового пулу для інтелектуального шлюзу граничного шару високощільного IoT
Keywords: Internet of Things; computer system; intelligent gateway; edge layer; IoT sensors; Інтернет речей; комп'ютерна система; інтелектуальний шлюз; граничний шар; сенсори ІоТ